Comparative Genomics and Phylogenetic Analysis Revealed the Chloroplast Genome Variation and Interspecific Relationships of Corylus (Betulaceae) Species - Yang, Zhen; Zhao, Tiantian; Ma, Qinghua; Liang, Lisong; Wang, Guixi (Frontiers in Plant Science, 2018)
Corylus L. is an economically and phylogenetically important genus in the family Betulaceae. Taxonomic and phylogenetic relationships of Corylus species have long been controversial for lack of effective molecular markers. In this study, the complete chloroplast (cp) genomes of six Corylus species were assembled and characterized using next-generation sequencing. We compared the genome features, repeat sequences, sequence divergence, and constructed the phylogenetic relationships of the six Corylus species. The results indicated that Corylus cp genomes were typical of the standard double-stranded DNA molecule, ranging from 160,445 base pairs (bp) (C. ferox var. thibetca) to 161,621 bp (C. yunnanensis) in length. Each genome contained a pair of inverted repeats (IRs), a large single-copy (LSC) region and a small single-copy (SSC) region. Each of the six cp genomes possessed 113 unique genes arranged in the same order, including 80 protein-coding, 29 tRNA, and 4 rRNA genes. C. yunnanensis contained the highest number of repeat sequences, and the richest SSRs in six cp genomes were A/T mononucleotides. Comparative analyses of six Corylus cp genomes revealed four hotspot regions (trnH-psbA, rpoB-trnC, trnF-ndhJ, and rpl32-trnL) that could be used as potential molecular markers. Phylogenetic analyses of the complete chloroplast genomes and 80 protein-coding genes exhibited nearly identical topologies that strongly supported the monophyly of Corylus and simultaneously revealed the generic relationships among Betulaceae. The availability of these genomes can offer valuable genetic information for further taxonomy, phylogeny, and species delimitation in Corylus or even Betulaceae plants.